Infiltration rate in several land covers in the educational forest of Muhammadiyah University of Mataram - Suhairin Suhairin; Aditya Ihwanul; Budy Wiryono; Muliatiningsih Muliatiningsih; Merita Ayu Indrianti; Handriany Erlianingsih (Universitas Muhammadiyah Mataram, 2025)
Infiltration rates across land cover vary depending on the type of land use. Several factors influencing soil physical properties include soil texture, organic matter, bulk density, porosity, aggregate stability, and water content. Low infiltration capacity impacts high runoff rates. Runoff has the potential to carry soil particles dislodged by rainwater to lower areas; this phenomenon is exacerbated if the land lacks shading vegetation. If continued, it will erode the topsoil, thinning the soil solum. The analysis results indicate that land covered by bananas, mixed gardens, heterogeneous forests, and shrubs has a very high infiltration rate. PCA results demonstrate a consistent relationship with basic soil science principles, particularly the relationship between soil structure, organic matter content, and infiltration rate. The positive correlation between porosity and infiltration rate reflects the role of the soil pore system in controlling water movement. The negative relationship between organic carbon and variables on the F1 axis indicates that increasing soil organic matter tends to be associated with changes in soil structure, leading to more stable and aggregative soil structures